Epidemiological and genetic characteristics associated with the severity of acute viral bronchiolitis by respiratory syncytial virus - Alfonso Eduardo Alvarez; Fernando Augusto de Lima Marson; Carmen Sílvia Bertuzzo; Clarice Weis Arns; José Dirceu Ribeiro (Elsevier, 2013)
Objective: to assess the epidemiological and genetic factors associated with severity of acute viral bronchiolitis (AVB) by respiratory syncytial virus (RSV). Data source: the key words "bronchiolitis", "risk factor", "genetics" and "respiratory syncytial virus", and all combinations among them were used to perform a search in the PubMed, SciELO, and Lilacs databases, of articles published after the year 2000 that included individuals younger than 2 years of age. Data synthesis: a total of 1,259 articles were found, and their respective summaries were read. Of these, 81 were selected, which assessed risk factors for the severity of AVB, and were read in full; the 60 most relevant studies were included. The epidemiologic factors associated with AVB severity by RSV were prematurity, passive smoking, young age, lack of breastfeeding, chronic lung disease, congenital heart disease, male gender, ethnicity, viral coinfection, low weight at admission, maternal smoking during pregnancy, atopic dermatitis, mechanical ventilation in the neonatal period, maternal history of atopy and/or asthma during pregnancy, season of birth, low socioeconomic status, Down syndrome, environmental pollution, living at an altitude > 2,500 meters above sea level, and cesarean section birth. Conversely, some children with severe AVB did not present any of these risk factors. In this regard, recent studies have verified the influence of genetic factors on the severity of AVB by RSV. Polymorphisms of the TLRs, RANTES, JUN, IFNA5, NOS2, CX3CR1, ILs, and VDR genes have been shown to be associated with more severe evolution of AVB by RSV. Conclusion: the severity of AVB by RSV is a phenomenon that depends on the varying degrees of interaction among epidemiological, environmental, and genetic variables. Resumo: Objetivo: avaliar os fatores epidemiológicos e genéticos associados à gravidade da Bronquiolite Viral Aguda (BVA) pelo Vírus Sincicial Respiratório (VSR). Fonte dos dados: foram utilizados descritores "bronchiolitis", "risk factor", "genetics" e "respiratory syncytial virus" e todas as combinações entre eles, nas bases de dados PubMed, SciELO e Lilacs publicados após o ano de 2000 e que incluíram indivíduos menores de dois anos de idade. Síntese dos dados: foram encontrados 1.259 artigos e lidos seus respectivos resumos. Destes foram selecionados 81 que avaliaram fatores de risco para a gravidade da BVA para leitura na íntegra, e foram incluídos os 60 estudos mais relevantes. Os fatores epidemiológicos associados com a gravidade da BVA pelo VSR foram: prematuridade, tabagismo passivo, baixa idade, ausência de aleitamento materno, doença pulmonar crônica, cardiopatia congênita, sexo masculino, etnia, coinfecção viral, baixo peso na admissão hospitalar, tabagismo materno na gestação, dermatite atópica, ventilação mecânica no período neonatal, antecedente materno de atopia e/ou asma na gestação, estação do nascimento, baixo nível socioeconômico, síndrome de Down, poluição ambiental, morar em altitude acima de 2.500 metros do nível do mar e parto cesariana. Em contrapartida, algumas crianças com BVA grave não apresentam nenhum desses fatores de risco. Neste sentido, estudos recentes têm verificado a influência de fatores genéticos relacionados à gravidade da BVA pelo VSR. Polimorfismos dos genes TLRs, RANTES, JUN, IFNA5, NOS2, CX3CR1, ILs e VDR têm-se mostrado associados com a evolução mais grave da BVA pelo VSR. Conclusão: a gravidade da BVA pelo VSR é um fenômeno dependente da interação entre variáveis epidemiológicas, ambientais e genéticas em seus diferentes graus de interação. Keywords: Bronchiolitis, Risk factors, Respiratory syncytial virus, Genetics, Palavras-chave: Bronquiolite, Fatores de risco, Vírus sincicial respiratório, Genética